2015
DOI: 10.14720/aas.2014.103.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seed size and aging on field performance of lentil (Lens culinaris Medik.) under different irrigation treatments

Abstract: A sub-sample of lentil (Lens culinaris 'Kimia') seeds was kept as bulk (S 1 ) and another sample was separated to large (S 2 ) and small (S 3 ) seeds. A sub-sample of each size was kept as control or high vigor seed lot (A 1 ) and the two other subsamples were artificially aged for 2 and 4 days (A 2 and A 3 , respectively). Field performance of these seeds was evaluated during 2011 and 2012. Yield components and grain yield of lentil decreased with decreasing water availability. The highest yield components (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…seedlings [26]. This is in agreement with our results and the results of another study on Borago officinalis, indicating the importance of seed priming for seed germination and field performance [27].…”
Section: Discussionsupporting
confidence: 93%
“…seedlings [26]. This is in agreement with our results and the results of another study on Borago officinalis, indicating the importance of seed priming for seed germination and field performance [27].…”
Section: Discussionsupporting
confidence: 93%
“…Biological yield and percentage ground cover had the highest positive correlations with grain yield per unit area (Table 5). This suggests that percentage ground cover and plant biomass have the major roles in determining final grain yield of mungbean, similar to that reported for rapeseed (Jabbarpour et al, 2012) and borage (Ghassemi-Golezani et al, 2013a).…”
Section: Correlationssupporting
confidence: 86%
“…In general, irrigation, as common agrotechnical treatment, was found to increase seed yield, as long as irrigation levels do not exceed crop water requirements (Szukała and Mystek 2006;Alderfasi and Alghamdi 2010;Hill et al 2011;Gresta et al 2017). However, some reports indicated that irrigation may also reduce vigor and sowing value of harvested seeds (Szukała and Mystek 2006;Faligowska and Szukała 2012;Ghassemi-Golezani et al 2012). It was demonstrated that seeds, seedlings, or mature lupin plants could differently respond to water excess; for example, in waterlogged soils, the seeds of L. angustifolius did not germinate and died within 4 days (Sarlistyaningsih et al 1995).…”
Section: Discussionmentioning
confidence: 99%